Haplomunnidae (Crustacea: Isopoda) reviewed, with a description of an intact specimen of Thylakogaster Wilson & Hessler, 1974 - Cunha, Marina R.; Wilson, George D.f. (Zootaxa, 2003)
The distribution and ecology of the isopod family Haplomunnidae Wilson, 1976 are reviewed with new records given for Thylakogaster Wilson & Hessler, 1974, Mid-Atlantic Ridge and east Pacific Ocean, and for Munella Bonnier, 1896, Mid-Atlantic Ridge and the eastern Atlantic near the African coast. The specimens of these two genera, collected from Lucky Strike (Mid-Atlantic Ridge), are the first record of the family from hydrothermal vent habitats. The systematics of the Haplomunnidae is updated and the synonymy of Aryballurops Gamô, 1983 with Haplomunna Richardson, 1908 is proposed. Thylakogaster lobotourus Wilson & Hessler, 1974 is redrawn from the first known intact specimen and additional description of the appendages is provided.